The pavements and slums of Dhaka - LeBeau, N; Tuckfield, H (Refugee Studies Centre, University of Oxford, 2017)
Almost half a million people every year seek refuge in Dhaka, compelled by a nexus of climate change, poverty and environmental degradation. Many end up on living on the pavements.